2018
DOI: 10.3389/fonc.2018.00575
|View full text |Cite
|
Sign up to set email alerts
|

Notch Signaling Regulates Mitochondrial Metabolism and NF-κB Activity in Triple-Negative Breast Cancer Cells via IKKα-Dependent Non-canonical Pathways

Abstract: Triple negative breast cancer (TNBC) patients have high risk of recurrence and metastasis, and current treatment options remain limited. Cancer stem-like cells (CSCs) have been linked to cancer initiation, progression and chemotherapy resistance. Notch signaling is a key pathway regulating TNBC CSC survival. Treatment of TNBC with PI3K or mTORC1/2 inhibitors results in drug-resistant, Notch-dependent CSC. However, downstream mechanisms and potentially druggable Notch effectors in TNBC CSCs are largely unknown.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 96 publications
2
55
0
Order By: Relevance
“…Besides, a recent study has also shown that sphingosine-1-phosphate (S1P) promotes CSC expansion via S1P receptor 3 and subsequent Notch1 activation in estrogen receptor (ER)-positive breast cancer cells 45 , suggesting that activation of Notch1 signaling in breast CSCs might be mediated through both Notch ligand-dependent and -independent pathways. Moreover, it is important to note that, in addition to the canonical nuclear signaling, Notch1 also drives non-canonical, cytoplasmic and mitochondrial signals in TNBC stem cells [46][47][48][49] , highlighting the generation of cell contextdependent diversity in the Notch1 signaling output. Nevertheless, the cause of the expression of Notch ligands in tumor perivascular niche is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, a recent study has also shown that sphingosine-1-phosphate (S1P) promotes CSC expansion via S1P receptor 3 and subsequent Notch1 activation in estrogen receptor (ER)-positive breast cancer cells 45 , suggesting that activation of Notch1 signaling in breast CSCs might be mediated through both Notch ligand-dependent and -independent pathways. Moreover, it is important to note that, in addition to the canonical nuclear signaling, Notch1 also drives non-canonical, cytoplasmic and mitochondrial signals in TNBC stem cells [46][47][48][49] , highlighting the generation of cell contextdependent diversity in the Notch1 signaling output. Nevertheless, the cause of the expression of Notch ligands in tumor perivascular niche is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Notch family proteins integrate with a range of signaling cascades that underlie pleiotropic outcomes of Notch signaling [15][16][17] . Here we provide evidence for spatial regulation of Notch4 signaling and its integration with a signaling cascade mediating protection from genomic damage.…”
Section: Discussionmentioning
confidence: 99%
“…Ligand-activated Notch undergoes a series of proteolytic cleavages, releasing the intracellular domain (Notch4 intracellular domain (NIC), which generally localizes to the nucleus [8][9][10] and complexes with cofactors recombination signal-binding protein-Jκ (RBPj-κ) and Mastermind like, to induce transcription of various genes 11,12 . Apart from this core canonical pathway, there are several reports of atypical ligand-independent and non-nuclear Notch signaling in diverse systems [13][14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Notch signaling is a key method to regulate the survival of CSCs in triple negative breast cancer. Treatment of triple-negative breast cancer with PI3K or mTORC1/2 inhibitors will produce drug-resistant Notch-dependent CSCs [40] . Most tumors are affected by EMT, the process of obtaining mesenchymal features from epithelial cells, during tumor progression.…”
Section: Discussionmentioning
confidence: 99%